الحماية القانونية الدولية للدبكة الفلسطينية بإعتبارها من التراث الثقافي غير المادي - شتيه, محمد (Revue jurisprudence; Vol. 12 No 02 (2019): مجلة الاجتهاد القضائي, 2020)
تعتبر الدبكة الشعبية الفلسطينية إحدى أبرز عناصر التراث الثقافي الفلسطيني غير المادي، والتي تعبر عن هوية الشعب الفلسطيني وتمييزه عن غيره من الشعوب؛ وفي محاولة من إسرائيل طمس هوية الشعب الفلسطيني تسعى إلى سرقة هذه الدبكة ونسبتها إلى إسرائيل، ناهيك عن لضييق على الفرق الفنية الفلسطينية، وفي هذا البحث تناولت إبراز تاريخ وأهمية الدبكة الفلسطينية وكيفية أدائها، وأهمية ومفهوم التراث الثقافي غير المادي بإعتبار الدبكة أحد عناصره، ومن ثم صور الإعتداءات على الدبكة، وآليات حمايتها من قبل منظمة الأمم المتحدة للتربية والثقافة والعلوم، بإعتبارها المتخصصة في هذا المجال. الكلمات المفتاحية: الدبكة الفلسطينية، التراث الثقافي الفلسطيني غير المادي، الحماية الدولية للدبكة الفلسطينية، التراث الثقافي غير المادي في القانون الدولي.   Abstract Palestinian Debka is one of the most important elements of the intangible palestinian cultural heritage, which expresses the identity of Palestinian people and distinguishes them from other people.  In an attempt by Israel to obliterate the identity of the palestinian people, it seeks to steal this Debka and attribute it to Israel, not to mention the restriction on the Palestinian artistic groups. In this research, I have examined the highliting of the history and importance of the palestinian debka,  how it is performed, the importance and the concept of the intangible cultural heritage, forms of the attacks on Dabkeh and its protection mechanisms by the United Nations Educational, Scientific and Cultural Organization (UNESCO) as it is specialist in this field. Key words: Palestinian Debka, the Intangible Palestinian Cultural Heritage, The International Protection of Palestinian Debka, The Intangible Cultural Heritage in the International Law, The International Protection of Intangible Heritage.